O toar dos professores: representações sociais sobre a prática docente - Araújo, Héllida Alcântara (2011)
This dissertation aims at analyzing the social representations on the teaching practice among teachers from the basic education first stages in a city of Paraíba. One intends to identify the representational contents of groups of teachers from both urban and rural areas in order to understand how these representations express themselves in different pedagogical moments. This study utilizes the theoretical-methodological approach of social representations based on the contributions by Serge Moscovici and by Denise Jodelet (2001). From its classical definition, one understands that the social representations constitute a process of creation, diffusion and change of knowledge socially constructed and shared in social groups daily discourse in their interactions, which permit the understanding and transformation of the reality to the construction of another common one for a social group. This research work is a qualitative one as it consists of an ethnographic case study based on the approach discussed by Marli André. The study utilizes the theoretical presuppositions adopted by Freire (1996) among other authors concerning the multidimensional characteristic attributed to the teaching practice. This study also highlights the teaching practice conception as a complex and heterogeneous activity full of formal concepts, norms, contradictions, tensions, dilemmas and diversities. The research accomplishment occurs in different moments: application of questionnaire, analysis of some school documents, observation, and focal group technique. The results have shown that teachers from both rural and urban areas share the same social representations although there are representational elements which are more evident in a group than another. As a conclusion, this research study has shown that the teaching practice is a highly complex activity by involving multiple dimensions and that are interconnected, complementing each other in the teaching action, such as: professional/institutional, cognitive, ethical, affectionate, political, philosophical and aesthetical.